Darya Likhareva Photograph of Empty Store Shelves - Likhareva, Darya::::::::: (2020)
One of four photographs Darya Likhareva took during the COVID-19 pandemic, this one depicting the empty shelves in an aisle of an unknown store. The contributor writes, "I have been taking daily photographs during this pandemic, and these are a collection of the most impactful ones (I think) that I've taken."